Regression Model for the Prediction of Risk of Pelvic Floor Muscle Weakness Among Older Adults. Issue 2 (April 2021) - Karkare, Prajakta; Mohapatra, Sidhiprada; Nandakumar, Girish
Abstract : Pelvic floor muscle (PFM) weakness is a common presentation among older adults, assessment of which is complicated by privacy issues, availability of perineometer, and lack of trained therapists. Several factors seem to influence PFM strength. Hence, this study developed an alternate method using a regression model to determine PFM strength among institutionalized older women using 27 independent variables. A total of 102 participants were assessed for their PFM strength using peritron perineometer. Age, years of menopause, pelvic surgical procedures, strength of hip muscles, and degenerative disc disorders were found to have a significant odds ratio and were included in the regression model ( r 2 = 0.484). It may be used as a simple and easy-to-administer method for the evaluation of PFM weakness.